Identification of the Heavy Metal Lead (Pb) in Red Macro Algae (Gracilia sp) In the waters of Tanjung Luar, East Lombok - Almahera, Almahera; Kurniawan, Ahmad Aldi; Maharani, B Firia; Himayanti, Yusfina Firia; Puspita, Novia Dara; Nurul Furqan, Baiq Repika (Universitas Islam Negeri Mataram, 2024)
Tanjung Luar Village is located in Keruak District, East Lombok Regency, West Nusa Tenggara, is a densely populated body of water human activity. In Tanjung Luar waters, household and ship waste dumped directly into the sea, polluting the local ecosystem. this condition important because people in the area consume a lot of produce marine catches, including red macroalgae (Gracilaria Sp). If Gracilaria Sp. is contaminated with levels of the heavy metal lead (Pb) that exceed threshold of 0.2 mg/kg, can be dangerous to human health impact on the nervous system, urinary system, endocrine system, problems gastrointestinal, and a very high risk of cancer. That thing based on BPOM Regulation No. 23 of 2017 (<0.2 mg/kg) for consumption materials. Therefore pollution and controlling the use of the heavy metal lead (Pb) important, especially in waters that play a supporting role life and food of local communities. The aim of this research is to determine the levels of the heavy metal lead (Pb) contained in the sample red macroalgae (Gracilaria Sp.) in Tanjung Luar Waters. Purposeful research to provide an overview and explanation of the issues discussed. This research uses the wet digestion method to identify heavy metal lead (Pb) of Gracilaria sp in waters Tanjung Luar, East Lombok. Next, levels of the heavy metal lead (Pb) were tested with ICP-OES spectrophotometry. With this method, researchers can identify the concentration of the heavy metal lead (Pb) in Gracilaria Sp. with a high level of accuracy. The results of the study showed that all sampling points of Gracilaria sp. did not exceed the threshold, which was less than 2 mg/kg. where at the sampling location point 1 had Pb concentrations of 0.072 ppm (location A), 0.063 ppm (location B), 0.057 ppm (location D), 0.051 ppm (location E) and 0.046 ppm (location F). for point 2 had Pb concentrations of 0.096 ppm (location A), 0.083 ppm (location B), 0.071 ppm (location C), 0.065 ppm (location E) and 0.059 ppm (location F). for point 3, the Pb concentrations were respectively 0.142 ppm (location A), 0.108 ppm (location C), 0.097 ppm (location D), 0.084 ppm (location E) and 0.070 ppm (location F)